EMI-Silent Operation of Triple Active Bridge Converters With Online Model-Free ZVS Optimization and RMS Current Reduction - Ahmed A. Ibrahim; Michele Darisi; Tommaso Caldognetto; Davide Biadene; Paolo Magnone; Paolo Mattavelli (IEEE Open Journal of Industry Applications)
Triple active bridge converter, an isolated multiport converter, connects three dc ports via a three-terminal high-frequency transformer, enabling zero voltage switching (ZVS) without the need for additional snubber circuits. However, under certain loading conditions ZVS is lost and rms currents increase. This article introduces a model-free, online optimization method using multi-dimensional ripple correlation control (MD-RCC) to ensure ZVS operation while reducing rms currents. The MD-RCC is an online model-free approach, providing robust performance against parameter uncertainties or operational variations. Two distinct methods are utilized to evaluate the cost function online. The first method involves the oversampling of the transformer currents. The second approach relies on the correlation between the EMI noise level and the hard switching of the devices, providing a simpler alternative to oversampling techniques. The proposed MD-RCC technique has been validated through both simulation and experimental testing on a 5 kW prototype, demonstrating its efficacy in optimizing ZVS, reducing EMI noise, and rms currents.